REVIEW OF THE TERMINATION OF EMPLOYMENT DISPUTE SETTLEMENT THROUGH MEDIATION IN THE ASAHAN DISTRICT MANPOWER SERVICE - Setiawan, Hery; Manurung, Mangaraja (Fakultas Hukum Universitas Djuanda, 2023)
Law enforcement and efforts to resolve Employment Termination Disputes are problems that exist in every district and city, one of which is in Asahan Regency. Writing this article aims to look at the process of resolving disputes over termination of employment and to see the obstacles the Asahan District Manpower Office has in suppressing the minimum number of Industrial Relations disputes. In writing this article, it was made using the Juridical Empirical research method for legal research. This method examines law from a real-world perspective and examines how it functions in society. The research location for writing this article is at the Manpower Office of Asahan Regency which is the inspiration for studying the laws that govern everyday life. The author in this study explores the living law through observation of the actions of the community, government and legal entities using secondary, primary and tertiary legal materials. There are several ways that employees of the Manpower Office of Asahan Regency have taken to reduce the number of industrial relations disputes. This includes counselling, record keeping and coaching.